Investigating ego modules involved in TGFβ3-induced chondrogenesis in mesenchymal stem cells based on ego network. (December 2016) - Wu, Jing-Guo; Jia, Qing-Wei; Li, Yong; Cao, Fei-Fei; Zhang, Xi-Shan; Liu, Cong
Graphical abstract: Highlights: A total of 15 ego genes were obtained from the DEN. Three ego modules (Module 3, Module 8 and Module 14) were identified, and all of them had statistical significances. Ego pathways, Cdc20:Phospho-APC/C mediated degradation of Cyclin A for Module 3, Mitohitic G1-G1/S phases for Module 8, and mRNA Splicing for Module 14. Abstract: Objective: This paper aimed to investigate ego modules for TGFβ3-induced chondrogenesis in mesenchymal stem cells (MSCs) using ego network algorithm. Methods: The ego network algorithm comprised three parts, extracting differential expression network (DEN) based on gene expression data and protein-protein interaction (PPI) data; exploring ego genes by reweighting DEN; and searching ego modules by ego gene expansions. Subsequently, permutation test was carried out to evaluate the statistical significance of the ego modules. Finally, pathway enrichment analysis was conducted to investigate ego pathways enriched by the ego modules. Results: A total of 15 ego genes were obtained from the DEN, such as PSMA4, HNRNPM and WDR77 . Starting with each ego genes, 15 candidate modules were gained. When setting the thresholds of the area under the receiver operating characteristics curve (AUC) ≥0.9 and gene size ≥4, three ego modules (Module 3, Module 8 and Module 14) were identified, and all of them had statistical significances between normal and TGFβ3-induced chondrogenesis in MSCs. By mapping module genes to confirmed pathway database, their ego pathways were detected, Cdc20:Phospho-APC/C mediated degradation of Cyclin A for Module 3, Mitotic G1-G1/S phases for Module 8, and mRNA Splicing for Module 14. Conclusions: We have successfully identified three ego modules, evaluated their statistical significances and investigated their functional enriched ego pathways. The findings might provide potential biomarkers and give great insights to reveal molecular mechanism underlying this process.